Opportunistic decision-making in government: concept formation, variety and explanation. (December 2017) - 6, Perri
The notion of opportunism is too often used loosely in policy and administrative research on executive decision-making: its various meanings are too rarely clearly distinguished. To make it useful for explanation, this article presents fresh concept formation work, clarifying the concept to recognize different kinds and degrees of opportunism. To illustrate the use of the refined concept, the article examines key decisions by British cabinets and core executives between 1945 and 1990. It proposes that neo-Durkheimian institutional theory can help to explain why different kinds of opportunism are cultivated in differently ordered administrations, so providing new insight into decision-making. Points for practitioners: The article provides a framework through which public managers can identify degrees and types of opportunism among the elected politicians they serve. It will help public managers to identify risks associated with such decisions, when they are asked to execute them.